EFFECT OF SERVICE QUALITY ON STUDENTS’ INTENTION TO PROVIDE FUNDING SUPPORT TO PRIVATE UNIVERSITIES IN GHANA: THE MEDIATING ROLE OF STUDENTS’ SATISFACTION - kraa, jerry jay (Advances in Social Sciences Research Journal, 2018)
Abstract The study investigates the effect of service quality on students’ intention to provide funding support to private universities in Ghana, the mediating role of students’ satisfaction. 600 students were selected from 6 private universities of which 421 responses were useable representing 70.16% response rate. Purposive and convenience sampling techniques were adopted in selecting respondents. Questionnaire was used for data collection. Stata version 13 and IBM Statistical Package for Social Sciences version 20 were the software used in data analysis. The study made use of Structural Equation Model for data analysis. Confirmatory Factor Analysis was also used for data purification in achieving fit indices. The research found that HEdPERF positively and significantly affects students’ satisfaction and their intention to provide funding support to Private University. Students satisfaction also positively and significantly impact on student’s intention to provide funding support to Private University. As regards the mediation effect, customer satisfaction partially mediates the relationship between HEdPERF and intention to provide funding support to Private Universities. Managers and policy makers must take action to improve students’ intention to provide funding support to Universities by promoting Reputation and Access issues in tertiary education.